The Owner’s Level of Knowledge about First Aid in Cat with Viral Diseases Symptomps at Satwagia RE Martadinata Clinic Bogor - Heryudianto Vibowo; Handeya Satiti (Journal of Applied Science, Technology & Humanities | JASTH, 2024)
There is a huge interest in cats in Indonesia, but this is not followed by the owner's knowledge regarding their care, which causes their pet cats to be easily infected with viral diseases. Owners often take cats with symptoms of viral disease to the veterinary clinic in serious conditions such as high fever, diarrhea for more than two days, not wanting to eat for more than two days, and severe dehydration. This research was conducted from 1 August to 31 October 2023 at the Satwagia RE Martadinata Veterinary Clinic. Primary data was obtained using a questionnaire method in the form of questionnaires to 100 respondents who came to the clinic and kept cats that had been infected with viral diseases. The data is presented descriptively to obtain an overview of the owner's knowledge regarding the first treatment of cats with symptoms of viral disease. The results of the research show that the level of knowledge of owners at the Satwagia RE Martadinata Bogor Animal Clinic regarding the first treatment of cats with symptoms of viral disease is good.